Effects of a movement training oriented rehabilitation program on symptoms, functional limitations and acromiohumeral distance in individuals with subacromial pain syndrome. Issue 5 (October 2015) - Savoie, Alexandre; Mercier, Catherine; Desmeules, François; Frémont, Pierre; Roy, Jean-Sébastien
Abstract Background Multiple factors have been associated with the presence of a subacromial pain syndrome (SPS), including deficits in performance of scapular and glenohumeral muscles. Such deficits can lead to inadequate kinematics and decreased acromiohumeral distance (AHD). Exercises that aim at correcting these deficits, such as movement training, were suggested to improve symptoms and functional limitations. To date, few studies have assessed outcomes following an intervention focused on movement training. Objectives Evaluate the effects of a rehabilitation program based on movement training on symptoms, functional limitations and AHD in individuals with SPS. Design Prospective single group pre-post design. Methods Twenty-five participants with SPS (SPS group) participated in a 6-week program. Twenty asymptomatic volunteers were recruited for normative AHD values (control group). Outcomes of both groups were evaluated at baseline and 6 weeks, i.e. immediately following intervention for the SPS group. Changes in symptoms and functional limitations for SPS group were assessed using the Western Ontario Rotator Cuff (WORC) index and Disability of the Arm Shoulder and Hand (DASH) questionnaire. Changes in AHD for both groups were assessed using ultrasonographic measures. Results Following the rehabilitation program, the scores on WORC and DASH were significantly improved (p < 0.001). AHD increased significantly in the SPS group (p = 0.019), especially in a subgroup with initial deficits (p < 0.001). Conclusion The rehabilitation program yielded improvements in symptoms and functional limitations in participants with SPS. Moreover, it led to an increase of the AHD – thus potentially decreasing subacromial compression, particularly in participants with an initially smaller AHD. The trial was registered at ClinicalTrials.gov: identifier – NCT02395770.